The tools of networked individuals: parallel patterns and strategies for governmental and research institutions. - Dutton, W; Eynon, R (2008)
Discussion of the role of the Internet in government and research tends to be 'institution-centric' in that e-Government and e-Research initiatives are both anchored in top-down strategies to provide information resources to citizens or researchers by place-based institutions, including governments and universities. In both institutional arenas, the diffusion of these services has been limited to small albeit growing proportions of their target audiences. In contrast, individuals with access to the Internet have taken bottom-up initiatives to obtain information and services from the space of flows of the Internet in ways that reach beyond the boundaries of both governmental and research institutions, but in ways that could compete with but also enhance existing institutions, such as by making them more accountable to their respective constituencies. Institutional actors in government and research need to more explicitly recognize and strategically adapt to the practices and tools taken up by networked individuals, such as by creating e-infrastructures that -- like the Internet -- enable rather than constrain bottom-up innovation.